Positive solutions for second order impulsive differential equations with Stieltjes integral boundary conditions - Jiang, J.; Liu, L.; Wu, Yong Hong (Springer, 2012)
In this paper, we study the existence of positive solutions for a singular second order impulsive differential equations with Stieltjes integral boundary conditions. By means of fixed point theorems, some results on the existence and multiplicity of positive solutions are obtained. Two examples are given to demonstrate the main results.